Indonesia’s Deterrence Strategy from the Perspective of the Total People’s Defense and Security System (Sishankamrata) - Mitro Prihantoro; Arifuddin Uksan (Department of Public Administration, 2026)
Indonesia faces a clear gap between its deterrence doctrine and the institutional capacity required to execute it within the Total People’s Defense and Security System known as Sishankamrata. The doctrine is comprehensive, yet systematic evaluation of how its core elements operate as an integrated deterrence system remains limited. These elements include ideological, political, economic, socio cultural, and defense security dimensions. This study examines Indonesia’s deterrence strategy through the Sishankamrata framework and assesses how it shapes national deterrence capacity against complex and evolving threats. The study applies a qualitative descriptive approach. Data collection took place from January to October 2025. Primary data consist of official doctrinal documents from the Ministry of Defense, national defense white papers, and strategic policy statements. Secondary data include peer reviewed journals and comparative studies of total defense systems implemented in Nordic states. Data analysis uses thematic mapping and interpretive document review. Validity is maintained through document triangulation and cross checking between official and academic sources. The findings show that Sishankamrata provides a coherent deterrence structure that integrates physical strength, moral resilience, and non conventional capabilities. However, several constraints remain. Coordination across sectors is not yet optimal. Institutional readiness varies. Public understanding of defense is still limited. Strategic communication lacks consistency and impact. The study concludes that Indonesia’s deterrence effectiveness depends not only on doctrine but on consistent institutional reform, active public participation, and credible strategic signaling across all sectors of national life.